Behaviour of unbonded reinforcement bar anchored in grouted spiral under increasing flexural bending - Yap, Sie Horng (2013)
This project report presents a research on the behaviour of beam with unbonded reinforcement bars being anchored into grouted spiral reinforcement at both ends and subjected to flexural loading. The use of spiral reinforcement is rather a new concept used in construction industry and still being studied on its application. Spiral reinforcement is believed to improve the bonding between concrete and steel, and currently being used in precast concrete connection. A series of laboratory testing was carried out to obtain required values which demonstrate the behaviour of beam anchored with spiral reinforcement. Total of six concrete beam specimens containing grouted spiral reinforcement were constructed and tested for flexural capacity, deflection and bond-slip of reinforcement. The parameters included in study were different inner diameter (33mm and 58mm) and pitch distance (15mm and 30mm) of spiral reinforcement. By using simple statistically and graphical method, analysis was carried out to determine the effectiveness of end anchorage in providing full flexural resistance to the concrete beam. The results were analysed for bond stress around the reinforcement bar under the effect of spiral confinement. Comparisons of results are carried to determine the influence of inner diameter and pitch distance of spiral reinforcement to the flexural capacity of concrete beam. From the test and analysis, it is found that even with unbonded reinforcement, the grouted spiral reinforcement at beam ends were able to provide full tension support to concrete beam in resisting flexural loading. Despite the unbonded section of reinforcement, the concrete beam able to sustain higher flexural load, estimate 23% more than typical concrete beam. The test also showed that increment in inner diameter or pitch distance of spiral reinforcement will reduce the bond strength between grout and reinforcement bar and subsequently reduced the flexural capacity of the concrete beam.